1979
DOI: 10.1113/jphysiol.1979.sp013026
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormones and the energetics of active sodium‐potassium transport in mammalian skeletal muscles.

Abstract: SUMMARY1. The steady-state heat production rate (1) of soleus muscles obtained from adult mice in various thyroid states was measured in a perfused microcalorimeter. The ouabain-suppressible fractions of E and 42K influx were compared and the energetic efficiency of active Na-K transport assessed.2. Hypothyroidism with plasma thyroxine concentrations below 1 jug/100 ml. was induced by pretreatment with 131I or perchlorate. In soleus muscles isolated from treated animals, mean E9 values were 2541 + 0 7 and 24-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
32
0
1

Year Published

1982
1982
1992
1992

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(38 citation statements)
references
References 26 publications
5
32
0
1
Order By: Relevance
“…Utilis6 ir la concentration molaire de 10 (Folke and Sestoft 1977), isolated rat soleus muscle and adipose tissue (Chinet et al 1977). and mouse soleus and diaphragm muscles (Biron et al 1979;Gregg and Milligan 1980 (Kleiber 1961 l"C (cold exposed) or 25"C (warm exposed) for 5 wk prior to muscle sampling. Warm-and cold-exposed sheep were fed to maintain body weight.…”
mentioning
confidence: 99%
“…Utilis6 ir la concentration molaire de 10 (Folke and Sestoft 1977), isolated rat soleus muscle and adipose tissue (Chinet et al 1977). and mouse soleus and diaphragm muscles (Biron et al 1979;Gregg and Milligan 1980 (Kleiber 1961 l"C (cold exposed) or 25"C (warm exposed) for 5 wk prior to muscle sampling. Warm-and cold-exposed sheep were fed to maintain body weight.…”
mentioning
confidence: 99%
“…A decrease in aK is compatible with the decrease in the ouabain-suppressible fraction of 42K uptake in hypothyroid mouse soleus (Biron et al 1979), and with the reduction in the intracellular K+ concentration of hypothyroid rat diaphragm (Ismail-Beigi & Edelman, 1973). (n = 61) (n = 57) n, number of fibres; P, significance of difference from untreated controls; n.s., not significant.…”
Section: Discussionmentioning
confidence: 70%
“…The number of Na+-K+ pump units decreases significantly in the skeletal muscles of hypothyroid mice (Biron, Burger, Chinet, Clausen & Dubois-Ferriere, 1979) and rats (Kjeldsen, Everts & Clausen, 1986;Everts & Clausen, 1988). Whether hypothyroidism and the resultant decrease in pump units is associated with changes in membrane potential (Vm) and intracellular sodium and potassium activities (a'a and a') of the muscles is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, McBride & Milligan (1985 a ) estimated that in sheep the ouabain-sensitive respiration of hepatocytes was about 35 YO, whereas Clark et al (1982) reported that in rat hepatocytes the ouabain-suppressible oxygen uptake was 2-8 '10. Similar discrepancies have been reported for muscle tissue (Asano et al 1976;Biron et al 1979;Gregg & Milligan, 1982). Furthermore, there are no estimates for the contribution of the Na pump to the basal or resting metabolic rate in the whole animal.…”
mentioning
confidence: 52%
“…reported that injection of ouabain into mice decreased 0, consumption by 20-25 YO, which is in agreement with our findings. Previous in vitro studies on the energy cost of the Na pump have been made on isolated tissues or cells and the results have been conflicting (Asano et al 1976;Biron et al 1979;Guernsey & Morishige, 1979;Gstraunthaler et al 1985;Milligan & McBride, 1985). Some of these conflicting results could be due to differences in the concentration of ouabain used.…”
Section: Discussionmentioning
confidence: 99%